Survei Minat Belajar Penjas dan Tingkat Kesegaran Jasmani Siswa Kelas X di SMK Pamor Cikampek Pada Masa Pandemi Covid 19 - Rizki Agus Pramana; Rekha Ratri J; M. Mury Syafei (Jurnal Ilmiah Wahana Pendidikan, 2021)
This study aims to determine the interest in learning physical education and the level of physical fitness of class X students at SMK Pamor Cikampek during the covid 19 pandemic. The research method used a survey method with questionnaires and physical fitness tests. For interest in physical education, there are categories of "very often" by 11.32% (6 students), "often" by 52.83% (28 students), "sometimes" by 32.08% (17 students), "rarely". ” is 3.77% (2 students), and “never” is 0.00% (0 students). Karawang Regency During the COVID-19 pandemic, it was in the good category "often" with an average (mean) score of 115.75. As for the results of the study, the level of physical fitness of class X students at SMK Pamor Cikampek, Cikampek District, Karawang Regency During the COVID-19 pandemic, it was in the "very good" category of 3.77% (2 students), "good" at 33.96% (18 students), “enough” was 35.85% (19 students), “poor” was 22.64% (12 students), and “very poor” was 3.77% (2 students). Based on the average score, which is 15.90% of the physical fitness level of class X students at Cikampek Pamor High School, Cikampek District, Karawang Regency During the COVID-19 pandemic, they were in the "enough" category with an average (mean) score of 15.90